Balanced maintenance fluids in PICU are safe and cost effective. Issue 6 (9th May 2013) - Sutherland, A; Playfor, S; Manaf, A
Abstract : Introduction: The use of hypotonic intravenous fluid in children is acknowledged as a cause of iatrogenic harm. 1 Fatalities have been documented since 1992. 2 In 2007 the National Patient Safety Agency (NPSA) released an alert recommending that the use of hypotonic solutions be reduced. 3 There has been some considerable debate relating to the harm caused by using 0.45% sodium chloride with 5% glucose and the more conventional adult fluids (0.9% sodium chloride and derivatives). The use of solutions containing potassium has been identified as a cost-pressure within paediatrics. 500 ml of 0.45% sodium chloride with 5% glucose and 10 or 20 mmol potassium chloride costs £4.50 per bag. A solution based on 0.9% sodium chloride costs £7.50 per 500 ml. These products are unlicensed. A balanced isotonic fluid with a paediatric license is available to us (Plasmalyte148–5% Glucose). This study aims to demonstrate that changing from traditional maintenance fluid (0.9% sodium chloride with 5% glucose or 0.45% sodium chloride with 5% glucose) to a new formulation (Plasmalyte-148 Glucose 5%) is safe, and cost-effective. Methods: Retrospective audit in a Paediatric Intensive Care Unit (PICU) comparing 2010–2011 and 2011–2012 examining usage, expenditure (expressed as a gross figure, and cost per unit of therapy) and population serum electrolytes using archived Biochemistry data. Results: Serum electrolytes showed no significant change between the two periods: Sodium: 141 mmol/l (2010–2011; range 95–187, median 140) to 143 mmol/l (2011–2012; range 126–190, median 141) Potassium: 3.99 mmol/l (2010–11; range 1.9–9.2, median 3.9) to 3.81 mmol/l (2011–2012; range 1.9–9.0, median 3.7) Chloride: 106 mmol/l (2010–11; range 70–142, median 105) to 106 mmol/l (2010–11; range 68–141, median 105) Between both periods there was a 35% increase in fluid consumption (2522 units in FY11/12; 1860 units in FY10/11) but average cost per unit fell by 57% (£1.83/unit in FY11/12; £4.18/unit in FY10/11) Hypotonic fluid usage and isotonic-hyperchloraemic fluid use was reduced by 50%. There were no reported cases of iatrogenic hyponatraemia in the period after introduction of the new balanced fluid. However there were three admissions to PICU from paediatric wards where fluid-associated hyponatraemia were considered significant contributing factors. Conclusions: Plasmalyte148–5% Glucose as the standard maintenance fluid for PICU is safe and effective; it has facilitated a reduction in the use of hypotonic fluids meeting Trust obligations under NPSA Safety Alert 22. There have been no documented cases of iatrogenic hyponatraemia in PICU since the adoption of this solution. There has been no change in electrolyte balance in the PICU patient population with the use of the balanced solution. Using a licensed balanced solution has reduced overall expenditure on maintenance fluids in PICU by 40% representing a saving in 1 year of £3200. We advocate the use of this balanced solution for all children in acute hospitals requiring intravenous fluids.